(untitled) (Physical Education, Health and Social Sciences, 2026)
This article critically examines the slogans associated with the Aurat March under the theme “Awareness or Misleading Narratives?” It explores whether these slogans genuinely promote women’s rights and social awareness or contribute to conceptual confusion and ideological misrepresentation within society. The study analyzes selected placards and slogans through a socio-cultural, psychological, and religious lens, particularly within the context of Pakistani society. The paper argues that while the discourse of women’s rights is essential and legitimate, certain expressions and slogans reflect a reactionary and unbalanced narrative that may conflict with established moral, cultural, and religious values. By evaluating the language, symbolism, and implications of these slogans, the study highlights how some narratives tend to oversimplify complex social issues, potentially leading to polarization rather than constructive dialogue. Furthermore, the article emphasizes the need for a balanced approach that acknowledges women’s legitimate rights while remaining aligned with ethical, social, and religious frameworks. It concludes that meaningful advocacy requires clarity, responsibility, and cultural sensitivity, rather than ambiguity or provocation, to ensure genuine awareness and positive societal reform.